M16 Blood and sputum eosinophils, interleukin 5 and bronchiectasis. (12th November 2019) - Chew, V; Davidson, R; Davison, J; Jiwa, K; Davies, G; Jones, G; De Soyza, A
Abstract : Aim: Bronchiectasis is thought to be a neutrophilic lung disease. However, increasingly it is recognised in some patients eosinophils may predominate. We have reported previously a significant minority of patients have eosinophilic predominant sputum cytology even in the absence of known asthma. As IL-5 is a key mediator of eosinophil activation, we aim to study the correlation between IL-5 and eosinophil in both serum and sputum. Method: 120 patients were recruited into the study from our regional bronchiectasis service. We report data on the first 51 fully analysed. The level of IL-5 in both serum and sputum were measured with the MSD Kits. Sputum eosinophil were counted and serum eosinophil were recorded from routine FBC. Data which includes IL-5 and eosinophil levels in both serum and sputum were analysed to find a correlation with each measurement. Result: Blood and sputum eosinophil showed a good correlation with a coefficient of 0.694. Interestingly no correlation was found for other comparisons with a coefficient of 0.042 between serum and sputum IL-5, 0.349 between serum IL-5 and serum eosinophil and 0.055 between serum IL-5 and sputum IL-5. Conclusion: Our data suggest there is a good correlation between sputum and blood eosinophil in bronchiectasis. We could not find a correlation between other markers. This may be due to the heterogeneity of bronchiectasis where only a certain subset of patients are predominantly eosinophilic driven and compartmentalization of inflammation within the lung separating it from systemic compartments. The study sample size is being increased in order to exclude a type 1 error. It is plausible that other cytokines beyond IL-5 contribute to eosinophilia in sputum.